1997
DOI: 10.1002/(sici)1097-0231(19971015)11:15<1677::aid-rcm926>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase derivatization of endohedral metallofullerenes R@C82 and R2@C80 (R = Nd, Ce)

Abstract: 1 The interest in these species is driven by the expectation that a whole new series of materials may be created, with properties tailored by altering the encapsulated atom.2 Researches on metallofullerenes developed slowly until the K-H method was used to prepare samples in bulk.3 Subsequently most of the rare-earth elements have been encapsulated in fullerene cages successfully, 4 and the isolation and characterization of these rare-earth metallofullerenes has been extensively studied.2 Up to now, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Liu und Mitarbeiter berichteten 1997 über die Funktionalisierung von M‐EMFs (M=Nd, Ce) mit Vinylacetat in einem Elektronenstoß‐Massenspektrometer 80. Im Massenspektrometer bildet sich das elektrophile C 2 H 3 O + ( m / z 43), das sofort an den Kohlenstoffkäfig addiert 80. Neben den m / z ‐Signalen für M@C 80 und M@C 82 (M=Nd, Ce) wurden auch die höheren Signale der Additionsverbindungen (+43 m / z ) beobachtet.…”
Section: Chemische Funktionalisierungunclassified
“…Liu und Mitarbeiter berichteten 1997 über die Funktionalisierung von M‐EMFs (M=Nd, Ce) mit Vinylacetat in einem Elektronenstoß‐Massenspektrometer 80. Im Massenspektrometer bildet sich das elektrophile C 2 H 3 O + ( m / z 43), das sofort an den Kohlenstoffkäfig addiert 80. Neben den m / z ‐Signalen für M@C 80 und M@C 82 (M=Nd, Ce) wurden auch die höheren Signale der Additionsverbindungen (+43 m / z ) beobachtet.…”
Section: Chemische Funktionalisierungunclassified
“…11 To date, however, no article has reported the spin-spin interactions and anisotropic magnetism of chemically functionalized EMFs having paramagnetic carbon cage structures. Furthermore, there have been only a few studies of chemical modifications of Ce@C 82 , 18j, 21,22 and to the best of our knowledge, none of the reports achieved structural elucidations of the derivatives. In view of the promising potential applications of EMFs in the nanotechnology area, it is very interesting and important to clarify the influence of chemical modifications of EMFs on their magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Two encapsulated metal atoms are frequently found in the C 80 -I h fullerene as this unstable isomer [24][25][26] is stabilised by forming M 2 @C 80 (M ¼ La, Ce, etc.) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] These metallofullerenes have been adapted for further usage by specific cage functionalization. [29][30][31] The motion of the dopants within the cage has also been shown to be manipulated with functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Ce 2 @C 80 was first reported over a decade ago, 38 but only a few follow-up studies have been reported. [38][39][40][41][42][43] The UV-Vis spectrum of Ce 2 @C 80 differs from the spectrum of the pristine C 80 cage, indicating that Ce 2 @C 80 has a different isomer than the empty cage (I h and D 2 , respectively), with the proposition that each Ce donates three electrons to the cage in Ce 2 @C 80 . 38,41 X-Ray photoemission spectroscopy confirms that Ce has the same +3 oxidation state in Ce 2 @C 80 and Ce@C 82 .…”
Section: Introductionmentioning
confidence: 99%